2009
DOI: 10.1073/pnas.0905127106
|View full text |Cite
|
Sign up to set email alerts
|

Structure–neurotoxicity relationships of amyloid β-protein oligomers

Abstract: Amyloid ␤-protein (A␤) oligomers may be the proximate neurotoxins in Alzheimer's disease (AD). ''Oligomer'' is an ill-defined term because many kinds have been reported and they often exist in rapid equilibrium with monomers and higher-order assemblies. We report here results of studies in which specific oligomers have been stabilized structurally, fractionated in pure form, and then studied by using a combination of CD spectroscopy, Thioflavin T fluorescence, EM, atomic force microscopy (AFM), and neurotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
663
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 712 publications
(738 citation statements)
references
References 32 publications
69
663
6
Order By: Relevance
“…From a biological and biomedical perspective, it is important to understand the conditions under which oligomeric clusters form, because such species exhibit high cytotoxicity (1,(29)(30)(31). Indeed, there is strong evidence that the disordered oligomers rather than fully grown fibrils are the main pathogenic species in protein aggregation diseases (31)(32)(33).…”
mentioning
confidence: 99%
“…From a biological and biomedical perspective, it is important to understand the conditions under which oligomeric clusters form, because such species exhibit high cytotoxicity (1,(29)(30)(31). Indeed, there is strong evidence that the disordered oligomers rather than fully grown fibrils are the main pathogenic species in protein aggregation diseases (31)(32)(33).…”
mentioning
confidence: 99%
“…It has been suggested that the physical properties of proteins (e.g., aggregate pattern and size) is a crucial determinant in mediating pathogenic toxicity [57,58]. This toxicity occurs independent of their sequences or lengths [59] in a manner that is similar to the aggregation of Aβ in Alzheimer's disease [60] or α-synuclein in Parkinson's disease [61]. Previous studies showed that Pam3-Cys, the synthetic N-terminus of ospA, self-assembled and showed aggregating potential in vitro assays [58,62], which can be related to brain tissue damage including the disruption of synaptic function.…”
Section: Advances In Lipoprotein Researchmentioning
confidence: 99%
“…Small oligomers of Aβ secreted from cell lines that overproduce Aβ 42 inhibit long-term potentiation in hippocampal synaptic transmission [32] and induces neuronal toxicity in mice [35]. Oligomeric forms of αS and Aβ inhibit mitochondrial activity [31,36]. Toxicity of Aβ 42 aggregates ebbs as monomers are depleted, but can be restored by the addition of fresh monomeric protein [31].…”
Section: Toxicity and Amyloid Formationmentioning
confidence: 99%
“…Methionine and tyrosine are easily modified by ROS. Oxidation of methionine 35 increases Aβ aggregation propensity [45] and tri-and tetrameric Aβ oligomers that are cross-linked by radical-induced dityrosine bridges are toxic to cells [36]. It is not clear whether oxidative stress and the generation of ROS is the primary pathologic event or whether it is a consequence of protein misfolding [46].…”
Section: Toxicity and Amyloid Formationmentioning
confidence: 99%
See 1 more Smart Citation